2018
DOI: 10.1080/09638199.2018.1549588
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of world trade from 1995 to 2014: A network approach

Abstract: This paper employs network analysis to study world trade from 1995 to 2014. We focus on the main connective features of the world trade network (WTN) and their dynamics. Results suggest that countries' efforts to attain the benefits of trade have resulted in an intertwined network that is increasingly dense, reciprocal, and clustered. Trade linkages are distributed homogeneously among countries, but their intensity (i.e. their value) is highly concentrated in a small set of countries. The main connective featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 62 publications
(90 reference statements)
0
14
0
1
Order By: Relevance
“…The behaviour of international trade flows, the impact of globalization on the international exchanges, the presence of a core-periphery structure or the evolution of the community centres of trade are just some of the issues addressed by the recent developments (Serrano et al 2007;Tzekina et al 2008;Fagiolo et al 2010;De Benedictis and Tajoli 2011;Blöchl et al 2011). Many works have dealt with the network from a multi layers perspective (Snyder and Kick 1979;Barigozzi et al 2011) or aim to emphasize financial implications of the world trade or contagion processes on the network (Wilhite 2001;Reyes et al 2008;Schiavo et al 2010;Fagiolo et al 2013;Fan et al 2014;Varela et al 2015;Giudici and Spelta 2016;De Benedictis and Tajoli 2016;Cepeda-López et al 2019;Cerqueti et al 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The behaviour of international trade flows, the impact of globalization on the international exchanges, the presence of a core-periphery structure or the evolution of the community centres of trade are just some of the issues addressed by the recent developments (Serrano et al 2007;Tzekina et al 2008;Fagiolo et al 2010;De Benedictis and Tajoli 2011;Blöchl et al 2011). Many works have dealt with the network from a multi layers perspective (Snyder and Kick 1979;Barigozzi et al 2011) or aim to emphasize financial implications of the world trade or contagion processes on the network (Wilhite 2001;Reyes et al 2008;Schiavo et al 2010;Fagiolo et al 2013;Fan et al 2014;Varela et al 2015;Giudici and Spelta 2016;De Benedictis and Tajoli 2016;Cepeda-López et al 2019;Cerqueti et al 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…closeness centrality) or random walk betweenness centrality (see . As the majority of countries in the WTN display a large number of linkages to other countries and low distances among them (see Cepeda-López, Gamboa-Estrada, León, & Rincón-Castro, 2018), most betweenness measures tend to be of limited informational value about cross-section differences between countries; moreover, most of them-in their standard formulation-overlook the weighted nature of the WTN. Our choice of algorithms is analogous to that of Ospina (2013).…”
Section: Network Centrality Analysismentioning
confidence: 99%
“…Fourth, taking into account that the emergence of global value chains has accompanied the integration of the world, we measure to what extent Colombia is important as an exporter to (importer from) key global buyers (suppliers) in the WTN. 7 Fifth, based on network centrality measures that capture global importance, 5 See Serrano and Boguñá (2003), Kali and Reyes (2007), Fagiolo et al (2010), Reyes et al (2010), Cassi, Morrison, andTer Wal (2012), De Benedictis, Nenci, Santoni, Tajoli, andVicarelli (2014), Xu and Qin (2015), Cepeda-López, Gamboa-Estrada, León, and Rincón-Castro (2018). 6 Alongside Fagiolo et al (2010), Ospina (2013), Kastelle and Liesch (2013), Beaton, Cebotari, Ding, and Komaromi (2017), and Soyyigit and Yavuzaslan (2018).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of an increasingly dense and interconnected network is unsurprising, but the patterns of clustering have stimulated research into the underlying drivers that have shaped these nonrandom relationships. Studies have found that while the global trade network has become more connected over time, the intensity of trade remains concentrated in a few powerful players (Cepeda‐López, Gamboa‐Estrada, León, & Rincón‐Castro, ). The presence of powerful players, network hubs and clusters indicate that certain countries tend to be “attracted” to each other, and thus tend to form deeper, denser and stronger ties (Serrano & Boguñá, ).…”
Section: Regional Integration and Economic Dynamicsmentioning
confidence: 99%